Actividad antifúngica del extracto etanólico de las hojas de Schinus molle L. “molle” sobre el crecimiento de Lasiodiplodia theobromae (Pat.) Griffon & Maubl., en condiciones de laboratorio. - Segura Contreras, Silvia Roxana (2015)
Was evaluated the antifungal activity of ethanol extract of the leaves of Schinus molle, on Lasiodiplodia theobromae. For this purpose the culture medium potato dextrose agar was prepared and then proceeded to obtain the extract of S. molle "molle" at concentrations of 0, 25, 30, 35% .The ethanol extract of "molle" found to have antifungal activity L. theobromae on the concentration of 30%. The results were analyzed by the percent inhibition of mycelial growth, analysis of variance and Tukey test. It is concluded that the extract of S. molle has antifungal activity on L. theobromae, under laboratory conditions. Key words: etanol extract, L. theobromae, S. molle, antifungal activity.